Death of a dreamer : a Hamish Macbeth mystery - Beaton, M. C. (New York : Mysterious Press, 2006)
Surprised that a newcomer to the Scottish Highlands has remained steadfast to her new home in spite of an inhospitable winter, constable Hamish Macbeth learns that the woman has deluded herself into believing that she is engaged to a local artist.
Keywords: MacBeth, Hamish (Fictitious character) -- Fiction; Police -- Scotland -- Highlands -- Fiction; Women -- Crimes against -- Fiction; Artists -- Fiction; Highlands (Scotland) -- Fiction; Mystery fiction